2004
DOI: 10.1001/archneur.61.6.919
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Transporter Loss Visualized With FP-CIT SPECT in the Differential Diagnosis of Dementia With Lewy Bodies

Abstract: Background: Dementia with Lewy bodies (DLB) is a common form of late-life dementia that can be difficult to differentiate from other disorders, especially Alzheimer disease (AD), during life. At autopsy the striatal dopaminergic transporter is reduced. Objectives: To examine the extent and pattern of dopamine transporter loss using iodine I 123-radiolabeled 2 ␤ -c a r b o m e t h o x y -3 ␤ -( 4 -i o d o p h e n y l ) -N -( 3fluoropropyl) nortropane (FP-CIT) with single-photon emission computed tomography (SPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
193
3
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(220 citation statements)
references
References 25 publications
15
193
3
9
Order By: Relevance
“…Our results showed almost perfect interobserver agreement between the two observers in visually interpreting 123 I-FP-CIT SPECT images, which is consistent with an earlier study using the same 4-point visual rating scale [21]. Other studies are also reported a high interobserver agreement for visual analysis when using only a dichotomous division of normal versus abnormal SPECT images [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed almost perfect interobserver agreement between the two observers in visually interpreting 123 I-FP-CIT SPECT images, which is consistent with an earlier study using the same 4-point visual rating scale [21]. Other studies are also reported a high interobserver agreement for visual analysis when using only a dichotomous division of normal versus abnormal SPECT images [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…For 123 I-FP-CIT, a consensus visual rating score was used as the classification variable as previously reported. 8,15 The ROC curve analysis revealed diagnostic characteristics of (0.80 ± 0.06, 72%, 90%) and (0.83 ± 0.06, 81%, 84%) for the multivariate SCA approach and 123 I-FP-CIT visual rating, respectively, indicating similar diagnostic accuracy in this cohort (D ¼ 0.02 ± 0.09, Z ¼ 0.3, P ¼ 0.80). Table 2 depicts the association between 123 I-FP-CIT imaging and the multivariate SCA measures in classifying AD and DLB using clinical diagnosis as the 'gold' standard.…”
Section: Multivariate Spatial Covariance Analysismentioning
confidence: 67%
“…In vivo striatum dopaminergic denervation with loss of presynaptic striatal dopamine transporter (DAT), as measured by single-photon emission tomography (SPECT) and PET, is a consistent finding among patients with probable DLB, compared to clinically normal controls and patients with Alzheimer's disease dementia (Walker et al, 2002(Walker et al, , 2004O'Brien et al, 2004;McKeith et al, 2007). While the dopaminergic degeneration has been widely documented to affect the striatum of patients with DLB (Walker et al, 2004;Klein et al, 2010), a cholinergic network alteration involving the striatum has been postulated in the Lewy body disease spectrum of disorders (Langlais et al, 1993) but its mechanism is still poorly understood (Bohnen and Albin, 2011).…”
Section: Discussionmentioning
confidence: 94%